Berdamai dengan Diabetes: Pengelolaan Stres untuk Meningkatkan Efikasi Diri Penderita Diabetes - Setyani Alfinuha; Hartanti Hartanti; Ktut Dianovinina (Universitas Islam Indonesia, 2021)
ABSTRACT: People with diabetes require complex and demanding daily medication adherence. If self-efficacy in dealing with diabetes is low, it might worsen the physical and psychological condition of people with diabetes. This study aims to determine the effect of cognitive-behavioral stress management in improving diabetes management self-efficacy. The participants of this study was middle-aged women with type 2 diabetes mellitus. This study employed mixed-method by combining the quantitative research method in the form of a single-case experiment and qualitative research method in the form of a case study. The study was conducted on the two participants who had low self-efficacy in carrying out care as diabetics. Cognitive-behavioral stress management interventions given to participants showed that participants experienced an increase in diabetes management self-efficacy.Key words: Self-efficacy, type 2 diabetes mellitus, cognitive-behavioral stress anagement, stress management